(untitled) (Eurasian Journal of Ecology, 2025)
The article primarily presents ecological analytical studies on the waste generated in the production areas of the Baku Steel Company. It was determined that during various steel casting and processing operations in several production areas of the enterprise, different types of waste are formed in gaseous-aerosol, liquid, and solid states, each with distinct compositions and properties. Based on our preliminary scientific research, the actual composition and concentration levels of harmful substances released into the atmosphere at different times in both the working and sanitary protection zones were identified. Additionally, the composition of industrial wastewater and solid wastes generated by the enterprise was analyzed. The gaseous emissions at Baku Steel Company were measured using a Drager Tubes LLG gas detector device, while the analyses of water samples taken before and after purification from various departments of the plant were conducted using the ICP-OES GBC Quantima device. The article also provides scientific explanations on the negative environmental and human health impacts caused by heavy metals present in the industrial waste formed in the production areas of this enterprise. Key words: ecological analytical assessments, steel casting, sanitary protection zone, working zone, industrial waste